Testing the mediating role of management commitment to enhancing workplace behaviour and personal compliance within the university environment - Saad, Mazni; Ong, Mohd Hanafi Azman; Mohamed Mohan, Noor Malinda; Abdul Rauf, Reeny Karlina (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In line with the 2020 Occupational Safety and Health (OSH) Master Plan, a continuous proactive commitment from the university’s management is called for to ensure that its campus community can enjoy working in an environment that is mutually trusting, happy, productive, and safe. This study investigates the managementcommitment of several local universities through the eyes of its students and staff totalling 221 respondents. Assessment of the three regression models found Management Commitment significantly mediating the Behavioral and Personal Compliance relationship. This increased Management Commitment level subsequently pushes the average agreement level that the students and staff have for Personal Compliance. That management commitment has a mediating role to play in the interaction of these variables in the university environment confirms the Social Exchange Theory, where the students and staff would give back to the university what they have taken as a token of appreciation for top management’s effort at looking after their well-being. This study implicates management commitment as a critical component for achieving safety, health, and well-being of every employee under its charge. Upholding OSH reflects an acceptance of all the priorities set out in the master plan that will nurture a working environment that cares about safety and health.